Answer:
The answer is 12a^3+2a²+23a+18 ....
Step-by-step explanation:
The given terms are:
(3a + 2)(4a² - 2a + 9)
Now multiply each value of second bracket with the first bracket:
=4a²(3a+2) -2a(3a+2)+9(3a+2)
=12a^3+8a²-6a²-4a+27a+18
Solve the like terms:
=12a^3+2a²+23a+18
Therefore the answer is 12a^3+2a²+23a+18 ....
Answer:
7 1/2
Step-by-step explanation:
2 1/2 ÷ 1/3
Change the mixed number to an improper fraction
2 1/2 = (2*2+1)/2 = 5/2
5/2 ÷ 1/3
Copy dot flip
5/2 *3/1 = 15/2
Changing back to a mixed number
2 goes into 15 7 times with 1 left over
7 1/2